(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study presents the design and finite-element analysis (FEM) of three reinforced cement concrete (RCC) column configurations under seismic effect, with the objective of quantifying how a central Sal-timber core alters the structural performance of an otherwise conventional RCC column. All three columns are of identical external size (300 × 300 mm) and clear height 3.0 m, fixed at both ends, and use M30 concrete, Fe500 steel, 4–16 mm φ longitudinal bars (steel ratio 0.89 %) and 8 mm φ ties at 150 mm c/c. The configurations are a plain RCC column (C1), and two timber-composite RCC columns with 100 × 100 mm (C2) and 150 × 150 mm (C3) Sal-timber cores. Each column is idealised as a fixed-fixed line member discretised into six Euler-Bernoulli beam elements, using transformed-section properties (modular ratios m = 7.30 for steel and n = 0.456 for timber). Axial capacity is computed per IS 456:2000, modal and elastic-buckling behaviour from the FEM stiffness, and seismic demand by the equivalent-static method of IS 1893 (Part 1):2016 for Zone V. The results show that, because the timber core sits near the neutral axis, flexural rigidity falls only 0.6 % (C2) and 3.1 % (C3) and lateral drift is practically unchanged, while self-weight drops 7 % and 16 % respectively, reducing seismic base shear and end moments by a similar margin. The principal penalty is a reduction in ultimate axial capacity of 6 % (C2) and 13 % (C3). All three columns remain short (buckling never governs), satisfy the 0.4 % drift limit, and plot safely within the P–M interaction envelope. The 100 × 100 mm timber core offers the best balance of weight and seismic-demand reduction with negligible loss of capacity.